Efficacy of cognitive restructuring technique on adjustment of social isolates in a sample of nigerian secondary school adolescences - Ncheke, Damian Chijioke; Nwosu, Nneka; Egenti, Nkechi Theresa; Enajedu, Esther E; Ede, Moses Onyemaechi; Umah, Sunday S; Omeje, GN; Ugwu, FA (Global Journal of Medical and Clinical Case Reports, 2021)
Objective: Of the study is to investigate the efficacy of Cognitive Restructuring Technique on Adjustment of Social Isolates in a sample of Nigeria Secondary School Adolescents. Methods: Pre-test post-test randomized control trial experimental design was adopted by the researchers for the study (60). Secondary school adolescents who were drawn through proportionate stratified randomly sampling technique constituted the sample for the study. The secondary school adolescents were randomly assigned to experimental (32) and (28) groups. Social Isolates Assessment scale for Adolescents (SIASA) and Adjustment Scale of Social Isolates (ASSI) were used for data collection. SIASA and ASSI were properly validated by experts in the test development and the internal consistency reliability indices of the items estimated as 0.82 and 0.86 respectively using Cronbach Alpha method. Before the commencement of the testing and treatment package, the researchers assured the participants of confidentiality of interactions and personal information as they work together in self-disclosure. Thereafter, pre-treatment assessment (pre-test) was conducted using the SIASA and ASSI in order to collect baseline data (Time 1). After that, the experimental group was exposed to 90 minutes of the Cognitive Restructuring Technique (CRT) program twice a week for a period of 6-weeks. The treatment took place between September and November 2019. Post-test (Time 2) assessment was conducted 1 week after the last treatment session. Besides, a follow-up assessment was conducted after two months of the treatment (Time 3). Data collected were analyzed using repeated measures analysis of variance. Results: The findings of the study revealed that the efficacy of cognitive restructuring technique on the adjustment of social isolates adolescents was significant at post-test and follow-up measures. One of the contributions of the findings is that if secondary school adolescents are not properly counseled, their social isolate behavior will continue to increase. Conclusion: The contribution among others is that Federal Government or relevant education authorities should provide enough guidance counselors in the various institutions of learning who will assist in the counseling of adolescents in the dangers of social isolate behaviour using CRT.